Evaluasi Kebijakan Pengelolaan Sampah Berbasis Zero Waste: Studi Kasus di Kabupaten Badung, Bali - Erinaldi; Ade Chandra; Angelina Ramadhani; Ulfa Muti’ah (Jurnal Riset Multidisiplin Edukasi, 2025)
The Zero Waste–based waste management policy in Badung Regency, Bali, represents the local government’s commitment to achieving sustainable environmental management and promoting a circular economy. This study is motivated by the increasing volume of waste in Badung, which reaches 547 tons per day, and the limited effectiveness of source-based waste management due to inadequate facilities and low community participation. The purpose of this research is to evaluate the implementation of the Zero Waste policy in Badung Regency by assessing its effectiveness, efficiency, adequacy, responsiveness, and accuracy, as well as identifying supporting and inhibiting factors. This study employs William N. Dunn’s policy evaluation theory using a qualitative descriptive approach through document analysis, literature review, and secondary data from government reports and media sources. The findings reveal that the Zero Waste policy has been relatively effective in raising community awareness and reducing dependence on landfills. However, it remains inefficient due to limited funding and infrastructure capacity. The main supporting factors are strong regulatory frameworks and local cultural values (Tri Hita Karana), while the key barriers include weak inter-agency coordination and low public participation. In conclusion, the success of the Zero Waste policy depends on strengthening cross-sectoral governance, fostering inclusive policy communication, and enhancing institutional and community capacity toward sustainable waste management.